AMENABILITY OF THE SUGARCANE VARIETY 2005 T 16 TO SHOOT TIP CULTURE - Jagadeesh, B.; Hemanth Kumar, M.; Reddi Shekhar, M.; Sudhakar, P. (Journal of Sugarcane Research, 2020)
The protocol for regeneration of plantlets through in vitro culture using shoot tip was established for a pre-released early maturing sugarcane variety, 2005T16. Inoculation of shoot tip explants, surface sterilized with 10% sodium hypochlorite for 20 min on MS medium containing 3.0 mg l-1 BAP, 2.0 mg l-1 IAA and 2.0 mg l-1 kinetin led to axillary bud initiation and establishment. The highest multiple-shoot induction of 88.89% frequency within 12.3 days was also observed on the same medium with production of 12.3 multiple-shoots per axillary shoot. The best rooting of 77.78% and 6.8 roots per shoot having a mean length of 3.76 cm were recorded for the shootlets on half strength MS medium supplemented with 6 mg l-1 NAA. During acclimatization the highest survival percentage was observed in vermicompost: soil: sand mixture in 1:1:1 ratio.